2008
DOI: 10.1530/eje-07-0608
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon association of germline mutations of RET proto-oncogene and CDKN2A gene

Abstract: Introduction: Calcitonin measurement is advised in the diagnosis of thyroid nodules, as it is an accurate marker of medullary thyroid carcinoma (MTC). C-cell hyperplasia (CCH)-induced hypercalcitoninemia cannot be distinguished from that induced by MTC, unless surgery is performed. Case: We report the clinical and biological features of a patient with a family history of cancer, including melanoma and pancreatic cancer, who had previously undergone surgery for melanoma. He presented the unusual association of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In contrast to majority of RET 804 (non-cysteine) mutation carriers who remain biochemically normal till the third decade of life (54), individuals with classical cysteine mutations (codon 634) show a positive pentagastrin test during the first decade of life (6,(62)(63)(64). Additional studies have also described HPTH in association with V804M (50,59,69,99) and V804L mutations (58,60). Their results differed from earlier findings in that the authors found no statistically significant difference between the groups in mean age at diagnosis and stage of C-cell disease including size of MTC (macroscopic or microscopic), bilaterality, presence of CCH and regional node involvement.…”
Section: Phenotype Expression: Cysteine Versus Non-cysteine Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to majority of RET 804 (non-cysteine) mutation carriers who remain biochemically normal till the third decade of life (54), individuals with classical cysteine mutations (codon 634) show a positive pentagastrin test during the first decade of life (6,(62)(63)(64). Additional studies have also described HPTH in association with V804M (50,59,69,99) and V804L mutations (58,60). Their results differed from earlier findings in that the authors found no statistically significant difference between the groups in mean age at diagnosis and stage of C-cell disease including size of MTC (macroscopic or microscopic), bilaterality, presence of CCH and regional node involvement.…”
Section: Phenotype Expression: Cysteine Versus Non-cysteine Mutationsmentioning
confidence: 99%
“…In 2004, Gibelin et al first reported HPTH in a French MEN 2A family harboring a V804M mutation (69). Additional studies have also described HPTH in association with V804M (50, 59, 69, 99) and V804L mutations (58, 60). Another extrathyroidal feature of MEN 2 is CNT, a feature of MEN 2B and less commonly MEN 2A (70).…”
Section: Non‐cysteine Ret 804 Mutation: Phenotypically Heterogeneous mentioning
confidence: 99%
“…It was first detected in an Italian pancreatic cancer patient 37 , then later in an Italian multiple primary melanoma patient 42 , and in a Brazilian familial melanoma patient with Italian ancestors 43 . Foppiani et al 44 detected the P48T mutation in an Italian patient with multiple endocrine neoplasia 2A (MEN 2A) syndrome and papillary thyroid carcinoma along with a RET proto-oncogene mutation. The patient had past history of melanoma and family history of melanoma, pancreatic carcinoma and several other malignancies.…”
Section: Discussionmentioning
confidence: 99%